Promotion of the Transition of Adult Patients with Childhood-Onset Chronic Diseases among Pediatricians in Japan - Ishizaki, Yuko; Higashino, Hirohiko; Kaneko, Kazunari (Frontiers in Pediatrics, 2016)
The transition of adult patients with childhood-onset chronic diseases (APCCD) from pediatric to adult healthcare systems has recently received worldwide attention. However, Japan is lagging behind European countries and North America as this concept of healthcare transition was introduced only 10 years ago. In Japan, before the introduction of this concept, APCCD were referred to as “carryover patients,” who were often considered a burden in pediatric practice. In the late 1990s, groups composed of pediatric nephrologists, developmental and behavioral pediatricians, pediatric nurses, and special education teachers researching the quality of life of adult patients with chronic kidney disease began to discuss the physical and psychosocial problems of APCCD. In 2006, a group of pediatricians first introduced the term “transition” in a Japanese journal. By 2010, a group of adolescent nurses had begun a specialized training program aimed at supporting patients during the transitional period. In 2013, the Ministry of Health, Labour and Welfare in Japan convened a research committee, focusing on issues related to social, educational, and medical support for APCCD, and the Japan Pediatric Society established a committee for the healthcare transition of APCCD and summarized their statements. Moreover, in 2013, the Tokyo Metropolitan Children’s Medical Center initiated ambulatory services for APCCD managed by specialized nurses. The concept of healthcare transition has rapidly spread over these past 10 years. The purpose of this article is to describe how this concept of healthcare transition has advanced in Japan, such that APCCD now experience a positive pediatric to adult healthcare transition.